KARAKTERISTIK FISIK DAN KOMPOSISI KIMIA KIMA PASIR (Hippopus hippopus) SEGAR DAN OLAHAN DARI PERAIRAN SAWAI MALUKU TENGAH - Bernita Silaban (Jurnal Perikanan Unram, 2024)
Giant strawberry clams are a type of clam that is still consumed today by coastal communities in Sawai Country. Eaten fresh or processed further. This research aims to determine the physical characteristics and chemical composition of fresh and processed Giant strawberry clams from Sawai waters, North Seram District, Central Maluku. The method used in this research is a structured observation method, observing each stage of the process, taking samples and measuring their quality in the laboratory. The physical parameters analyzed include morphometric measurements. Environmental parameters include: temperature, pH and salinity. The chemical composition analyzed included water content, protein, fat, carbohydrate ash and weight loss in fresh giant strawberry clams and strawberry clams which were processed by: steaming, frying and drying. The research results showed that giant strawberry clams from Sawai waters had a diameter of 11-36 cm and a weight of 0.24-3.6 kg. Water temperature ranges from 29-30ºC, pH 7.5-7.8 and salinity 32-33 ppt. The average protein, ash and fat content of sand clam meat processed by frying, steaming and drying is higher than fresh clam meat, while the water content of clam meat after frying, steaming and drying becomes lower. Processed clam meat also experiences weight loss compared to fresh ingredients. The highest protein and ash content was found in dried sand clams at 44.8% and 4.83%, the highest fat content was in fried sand clams at 13.67%, and the lowest water content was in dried giant strawberry clams at 45.02 %, while the highest weight loss was found in dried clams with a shrinkage of 71.79% and the lowest in fried clams at 46.21%.